What have we learned from Linxian esophageal cancer etiological studies? - Wang, Shao‐Ming (Thorac Cancer, 2019)
Esophageal cancer is the sixth leading cause of cancer death in the world. Esophageal squamous cell carcinoma (ESCC) accounts for 90% of esophageal cancer cases, over half of which occur in China. Linxian, a county located in the North Central Taihang Mountain range, has the highest ESCC mortality rate, which may be the leading cause of death in this area. In a decades‐long research program in Linxian, Chinese and international scientists have exerted great efforts to describe the epidemiological characteristics and elucidate the etiology of ESCC. A systematic review and summary of the current knowledge gained from previous research is informative for future ESCC prevention and control in similar populations, and may be translated to other high‐incidence countries, such as Brazil, Iran, Malawi, and South Africa. As ESCC is a major cause of cancer death, more research is required in China and in other high‐incidence countries to deepen our understanding of the etiology of ESCC and develop preventative strategies.